2017
DOI: 10.4081/gh.2017.524
|View full text |Cite
|
Sign up to set email alerts
|

Variability of nutrients intake, lipid profile and cardiovascular mortality among geographical areas in Spain: The DRECE study

Abstract: It has often been suggested that cardiovascular mortality and their geographical heterogeneity are associated with nutrients intake patterns and also lipid profile. The large Spanish study Dieta y Riesgo de Enfermedades Cardiovasculares en España (DRECE) investigated this theory from 1991 to 2010. Out of the 4,783 Spanish individuals making up the DRECE cohort, 220 subjects (148 men and 72 women) died (4.62%) during the course of the study. The mean age of patients who died from cardiovascular causes (32 in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…In addition, all regions saw a progressive increase in the consumption of this type of food (5.2–11%) during the 17 years of the study, similar to the overall increase in Spain. The Canary Islands is one of the regions with higher relative consumption of ultra-processed foods, which is in agreement with the dietary pattern found in other studies on this region, in which it has been characterized by high intakes of fats and carbohydrates (present at high levels in UPFs) with respect to other regions of Spain [ 76 ]. The north, north-west, and west regions showed worsening in their dietary patterns, being the regions with the highest increases in UPF consumption over time, and reaching the highest percentages of intake in 2008 (36%, 35.5%, and 34% of total intake, respectively) together with the Canary Islands.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, all regions saw a progressive increase in the consumption of this type of food (5.2–11%) during the 17 years of the study, similar to the overall increase in Spain. The Canary Islands is one of the regions with higher relative consumption of ultra-processed foods, which is in agreement with the dietary pattern found in other studies on this region, in which it has been characterized by high intakes of fats and carbohydrates (present at high levels in UPFs) with respect to other regions of Spain [ 76 ]. The north, north-west, and west regions showed worsening in their dietary patterns, being the regions with the highest increases in UPF consumption over time, and reaching the highest percentages of intake in 2008 (36%, 35.5%, and 34% of total intake, respectively) together with the Canary Islands.…”
Section: Discussionsupporting
confidence: 90%
“…The recently published DRECE study ( Diet and Risk of Cardiovascular Diseases in Spain ) prospectively evaluated the nutrient consumption and lipid profile of the diets of 4783 individuals by geographical area, between 1991 and 2010. Researchers found that the East and Southern areas of Spain had the highest fat intake, coupled with a high unhealthy lipid profile rate and cardiovascular mortality [ 12 ]. In addition, micronutrient intakes can be seriously compromised by poor or unbalanced dietary patterns, especially for those target population groups in which requirements are increased (i.e., women of childbearing age, children, and seniors).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, when assessing food consumption, the potential recall bias introduced by respondents in reporting their diets is strongly associated with a tendency to overestimate food consumption accepted as healthy and underestimate the least healthy food. This must be taken into account [ 12 ]. It is crucial to improve the tools for studying and assessing the energy intakes and losses of “free living” independent subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disorders of glucose homeostasis and lipid metabolism are commonly seen in CVDs and T2DM. Lipid profile abnormalities including representative markers such as triglyceride (TG), high-density lipoprotein-cholesterol (HDL-C), and low-density lipoprotein-cholesterol (LDL-C), are important indicators of cardiac metabolic risk and play a significant role in the development of CVDs 6. Insulin (INS) resistance is the main etiology and pathogenesis of T2DM 7.…”
Section: Introductionmentioning
confidence: 99%